2017
DOI: 10.1002/art.40047
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Treatment of Tumor Necrosis Factor–Transgenic Mice With Anti–Tumor Necrosis Factor Restores Lymphatic Contractions, Repairs Lymphatic Vessels, and May Increase Monocyte/Macrophage Egress

Abstract: Background Recent studies have demonstrated that there is an inverse relationship between lymphatic egress and inflammatory arthritis in affected joints. As a model, TNF-transgenic (TNF-Tg) mice develop advanced arthritis following draining lymph node collapse, and loss of lymphatic contractions downstream of inflamed joints. As it is unknown if these lymphatic deficits are reversible, we tested the hypothesis that anti-TNF therapy reduces advanced inflammatory-erosive arthritis, associated with restoration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(82 citation statements)
references
References 29 publications
3
73
0
Order By: Relevance
“…Experimental studies have revealed that immune cell-derived pro-inflammatory mediators released during an acute immune reaction, including TNFα, IL1β, and IFNγ but also nitric oxide (NO . ) produced at high levels by inducible nitric oxidase synthase (iNOS)-expressing cells, leads to lymphatic transport dysfunction 156 . Indeed, in vivo imaging studies have shown that inflammatory cytokines induce button to zipper transformation of LEC junctions and acute inflammation is often associated with reduced precollector/collector pumping with a reduction of the frequency and/or amplitude in lymphangion contractions.…”
Section: Box 3 Immune Cell Regulation Of Lymphatic Function and Remomentioning
confidence: 99%
“…Experimental studies have revealed that immune cell-derived pro-inflammatory mediators released during an acute immune reaction, including TNFα, IL1β, and IFNγ but also nitric oxide (NO . ) produced at high levels by inducible nitric oxidase synthase (iNOS)-expressing cells, leads to lymphatic transport dysfunction 156 . Indeed, in vivo imaging studies have shown that inflammatory cytokines induce button to zipper transformation of LEC junctions and acute inflammation is often associated with reduced precollector/collector pumping with a reduction of the frequency and/or amplitude in lymphangion contractions.…”
Section: Box 3 Immune Cell Regulation Of Lymphatic Function and Remomentioning
confidence: 99%
“…Inducible NOS directly affects lymphatic muscle cells via excess nitric oxide . We observed that in mice carrying the tumor necrosis factor transgene (TNF‐Tg), a model of rheumatoid arthritis (RA), macrophages were attached to LECs in the collecting lymphatic vessel that drains the inflamed joints . However, whether macrophages affect LEC function directly remains to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…When used in combination with adjuvant-induced arthritis, and genetic models (such as TNF-Tg mice), the CIA rat model provides an efficient means for predicting therapeutic efficacy in humans [38]. Since completing our work, another study in TNF-Tg animals has shown that systemic IP administration of anti-TNF drugs increase the lymphatic pump [14], in agreement with our data on early CIA progression in rats treated with etanercept versus untreated CIA rats. Extension of this work to adjuvant-induced arthritis, genetic models of RA, and human RA patients remains to be shown.…”
Section: Discussionmentioning
confidence: 99%